PENERAPAN STRATEGI PEMBELAJARAN ACTIVE KNOWLEDGE SHARING DALAM PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Moh. Afiful Hair; Mohammad Hadir (STAI Nusantara Banda Aceh, 2025)
This research was motivated by the low achievement of student learning outcomes in Islamic Religious Education (PAI) subjects at SMP Negeri 2 Proppo Pamekasan, which shows the need for implementing innovative learning strategies. The focus of this research is the application of the Active Knowledge Sharing (AKS) strategy in improving PAI learning outcomes, as well as identifying supporting and inhibiting factors that arise in the process. The aim of this research is to describe the implementation of the AKS strategy in class IX SMPN 2 Proppo, as well as explain the contribution of this strategy to improving student learning outcomes. The type of research used is qualitative research with a phenomenological approach. Primary data sources were obtained through interviews with school principals, PAI teachers and students, as well as direct observation of teaching and learning activities. Secondary data is supported by documentation in the form of school profiles, learning tools and grade archives. Data collection techniques were carried out using participant observation, in-depth interviews, and documentation studies. The data obtained was analyzed through data reduction, data presentation, and drawing conclusions. The results of the research show that the implementation of the Active Knowledge Sharing learning strategy in Islamic Religious Education subjects at SMP Negeri 2 Proppo Pamekasan is effective. This strategy encourages students to be more active, dare to discuss and share knowledge with each other so that understanding of the material increases and the class atmosphere becomes conducive and participatory. Supporting factors include student enthusiasm and enthusiasm, a dynamic classroom atmosphere, school support, and teacher creativity. However, there are still obstacles such as differences in academic abilities, lack of self-confidence for some students, limited discussion time, and diverse family backgrounds. Overall, this strategy contributes positively to increasing student participation and learning outcomes, although further efforts are still needed to overcome existing obstacles so that its implementation is more optimal.